Living With Less - The Documentation of a Personal Journey - Wang, Nancy (Auckland University of Technology, 2013)
As the world continues to expand in every measure, pressure in its sustainability also rises (Lam, 2007; O’Brien, 2010). There is a need to change our mentality from “Bigger is better” towards “Less is more” (Hayden, 2010 ; Hoak; Kiviat, 2009; Koch, 2009). Currently, majority of objects in the home exist within a complex network that includes other things. The acquisition of products that satisfy our specific needs often necessitates the purchase of additional ones. Thus our need for individual things often is in fact a need for a network of objects that are dependent on each other (Boradkar, 2010). This in term has led to the panorama on majority of today’s home interior dominated by an invasion of useful and useless objects which block out all perception of space (Bertoni, 1998). The practicality of living a minimalist life becomes questionable even if it is underpinned by a strong philosophical value. The nature of this project focuses on the concept of minimalist living. It involves an exploration and documentation on my personal understandings of minimalism and dematerialization as I explore into the role of everyday utilitarian objects in contributing towards minimalist lifestyle.
Keywords: Small space living; Furniture